Twin Deficit Phenomena in the Two Government Eras in Indonesia - Wibowo, Muhammad Ghafur (Jurnal Analisis Bisnis Ekonomi, 2020)
The aim of this study is to analyze the development of the budget deficit and current account deficit in Indonesia in the era of President SBY and President Jokowi and to compare between the two eras. This study also analyzes the relationship of twin deficits to the Gross Domestic Product (GDP) and the interest rate (r). The analytical tool used was independent t-test (for comparison) and Vector Auto-Regressive (VAR). The data used comes from the International Monetary Fund (IMF), 2004:Q1-2018: Q3. The result showed that the budget deficit was the same in the two eras of government, but the trade balance deficit in the era of President Jokowi was far higher than before. The budget deficit has a significant effect on the trade balance deficit but does not apply otherwise (no causality). Variable gross domestic product and interest rates significantly influence both types of deficits.